Does the sentiment of investors explain differences between predicted and realized stock prices?. Issue 3 (1st August 2016) - Spilioti, Stella N.
Abstract : Purpose: The purpose of this paper is to use the Barberis et al. (1998)'s valuation model to calculate the fundamental value of a stock and examine whether the differences between predicted and realized stock prices are explained both by psychological factors (that affect investor reaction to information) and by key macroeconomic variables. Design/methodology/approach: This paper adopts a time-series analysis, as well as a panel data approach, to examine whether the price deviations from fundamental values are because of macroeconomic and psychological factors, using data from the London Stock Exchange. Findings: The results indicate that these differences are explained by important macroeconomic variables, as well as by the sentiment of investors (that is used as a proxy of the psychological factors). Originality/value: Based on the above results, this paper suggests that the price deviations from fundamental values are not treated as model estimation errors as proposed by Penman and Sougiannis (1998) but rather as deviations that are because of psychological factors, as well as to macroeconomic conditions.